ENTREPRENEURIAL EDUCATION FOR DIFFERENTLY ABLED PEOPLE IN INDIA - Rajamohan, S.; Devi, E. Saranya (International Journal of Psychosocial Rehabilitation, 2020)
The opportunity for productive self-employment, education program seeks to raise incentive for wage jobs in government agencies. Many trained rural young people move continuously to city and towns in pursuit of employment, which are not adequate to fulfill the demands of all the aspirants due to slow economic growth and rise in population. Particularly the differently abled people is difficult to get the entrepreneurial education from the existing schemes and some vocational programmes. Hencethis paper made an attempt to explore the existing opportunities pertained to the entrepreneurial education and the various schemes that associated to develop the entrepreneurial skill of the disabled people in India.